Environmental control of Vibrio spp. abundance and community structure in tropical waters - Wong, Yi You; Lee, Choon Weng; Bong, Chui Wei; Lim, Joon Hai; Narayanan, Kumaran; Sim, Edmund Ui Hang (Oxford University Press, 2019)
We measured Vibrio spp. distribution and community profile in the tropical estuary of Port Klang and coastal water of Port Dickson, Malaysia. Vibrio spp. abundance ranged from 15 to 2395 colony forming units mL-1, and was driven by salinity and chlorophyll a (Chl a) concentration. However, the effect of salinity was pronounced only when salinity was <20 ppt. A total of 27 Vibrio spp. were identified, and theVibrio spp. community at Port Dickson was more diverse (H' = 1.94 ± 0.21). However species composition between Port Dickson and Port Klang were similar. Two frequently occurring Vibrio spp. were V. owensii and V. rotiferianus, which exhibited relatively higher growth rates (ANCOVA: F > 4.338, P < 0.05). Co-culture experiments between fast- and slow-growing Vibrio spp. revealed that fast-growing Vibrio spp. (r-strategists) were overwhelmed by slower-growing Vibrio spp. (K-strategists) when nutrient conditions were set towards oligotrophy. In response to resource availability, the intrinsic growth strategy of each Vibrio spp. determined its occurrence and the development of Vibrio spp. community composition. © FEMS 2019.